Descriptive Study Analyzing Medical and Surgical Methods of Terminating First Trimester Pregnancy - Raut, Bhaktabatsal; Acharya, Shreedhar (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: This study was conducted to analyze the medical and surgical methods of first trimester of pregnancy. MATERIAL AND METHODS: A hospital based retrospective study done at Lumbini Zonal Hospital, Butwal over the period of one year, where all the women who had first trimester abortion services were analyzed. Age, parity, education status, failure rates and post abortion contraception were analyzed. RESULTS: There were total of 478 women who had abortion services, of which 244 women had medical method of abortion. Among them 4.89% were teenagers and 11.29% were primigravida and 6.9% were uneducated. The failure rate for medical method was 9% and for surgical method was 1.7%. Most women at their post abortion period asked for condoms, followed by DMPA, IUD and OCP as a method of contraception. CONCLUSION: Failure rate of medical method was high and acceptance of long acting post abortion contraception was low. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, page: 1-5